2022
DOI: 10.1186/s12859-022-04894-6
|View full text |Cite
|
Sign up to set email alerts
|

High expression of cuproptosis-related SLC31A1 gene in relation to unfavorable outcome and deregulated immune cell infiltration in breast cancer: an analysis based on public databases

Abstract: Cuproptosis induction represents a promising alternative for immunotherapies and targeted therapies in breast cancer. This study aimed to investigate the prognostic and biological significance of cuproptosis-related genes in breast cancer. In the current study, we examined the transcriptional and clinical data of 13 cuproptosis-related genes in patients with breast cancer from TCGA database. We found that genes DLAT, SLC31A1, ATP7A and ATP7B were significantly related to the overall survival (OS) of breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Targeting necroptosis, pyroptosis, and ferroptosis to develop new anticancer medications for therapeutic use has been a long process, and recently, compounds inducing cuproptosis have shown promise as anticancer strategies [225,226]. In Table 1, we summarize 85 types of therapeutic agents that exert an effect on the mechanisms of newly discovered RCD modalities that have been tested in vivo and/or in vitro.…”
Section: Agents Targeting Novel Cell Death Pathwaysmentioning
confidence: 99%
“…Targeting necroptosis, pyroptosis, and ferroptosis to develop new anticancer medications for therapeutic use has been a long process, and recently, compounds inducing cuproptosis have shown promise as anticancer strategies [225,226]. In Table 1, we summarize 85 types of therapeutic agents that exert an effect on the mechanisms of newly discovered RCD modalities that have been tested in vivo and/or in vitro.…”
Section: Agents Targeting Novel Cell Death Pathwaysmentioning
confidence: 99%
“…As previously described, SLC31A1 mediates copper entry into cells while ATP7A and ATP7B mediate copper exit from cells, all functioning as copper carriers that closely related to the shuttle of copper [ 115 , 118 , 119 ]. High expression of SLC31A1 has been considered to be associated with poor clinical outcome of BRCA patients by two independent researches [ 120 , 128 ]. Researchers also found that the microsatellites of SLC31A1 and ATP7B were associated with lung cancer risk, suggesting that the expression levels of copper homeostasis-related genes may also influence the process of lung cancer development [ 99 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, copper importer SLC31A1 was significantly and positively associated with TEX phenotypes and checkpoint genes, while copper exporters, ATP7A and ATP7B, were negatively correlated with TEX phenotypes and checkpoint genes. Recently, two pieces of research also demonstrated that SLC31A1 -dependent copper absorption increases the malignancy grade of pancreatic and breast cancers ( Yu et al, 2019 ; Li et al, 2022 ). We also observed that three anti-cuproptosis genes ( CDKN2A , GLS and MTF1 ) were positively associated with TEX characteristics.…”
Section: Discussionmentioning
confidence: 99%